(untitled) (Indo-MathEdu Intellectuals Journal, 2024)
This study aims to evaluate the effectiveness of audio-visual learning media on Biology learning in junior high school. The method used is literature study by analyzing articles, books, and relevant literature sources. The data sources that will be used in this study are scientific articles, books, journals, research reports, and other literature sources that are relevant and related to the use of audio-visual learning media in biology learning. The data analysis method used in this study is literature analysis or systematic literature review. The results of the study show that the use of audio-visual learning media significantly improves students’ understanding in learning Biology. This medium helps students better visualize complex biological concepts, such as fertilization and embryonic development. In addition, audio-visual learning media also increases student involvement in the learning process, making it more interactive. However, there are several challenges in the use of audio-visual learning media, such as limited access to technology in some schools and high multimedia content development costs. Therefore, it is recommended that schools improve their technological infrastructure and train teachers in the effective use of this medium. The implication of this study is that audio-visual learning media can be used effectively to improve students’ understanding of complex biology materials